(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Concrete roads are very common and can provide safe and smooth traffic. Thanks to the use of concrete on the roads it has become a very good quality of life and low maintenance. However, concrete roads may be cracked, cracked, and the concrete weakened and malfunctioned. To alleviate these problems Fiberglass installation can provide significant concrete advantages. The study “Use of Separated Ropes in Solid Roadways” was conducted to improve the quality of concrete roads. In this study the fiber used was polypropylene fiber and polyester fiber. The concrete mix used is M25. In just one example, concrete mixes were tested for compressive strength, flexural strength and strength split strength. In the second specimen 1.6% polypropylene fiber was added to the concrete mixture and tested in three similar tests. In the third sample 0.4% of polyester fiber is applied to the concrete mix and tested for compressive strength, flexural strength and tensile strength is divided. In the fourth specimen both 1.6% polypropylene fiber and 0.4% polyester fiber were mixed with concrete mix and three tests were tested. Road transport is undoubtedly the nation’s way of life and its development is of paramount importance. Small traditional paraffin and its maintenance requirements and rehabilitation performance indicate the size of the concrete concrete areas. There are several advantages of cement concrete for small stone concrete. This paper focuses on the POLYMER FIBER REINFORED CONCRETE PAVEMENTS, a recent development in the field of reinforced concrete design. Comparative studies of these conventional concrete routes were performed using Polypropylene fiber waste as fiber reinforcement